1996
DOI: 10.1159/000211386
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Absorption, Excretion and Metabolism of All-<i>trans</i>-Retinoyl β-Glucuronide and of AII-<i>trans</i>-Retinoic Acid in the Rat

Abstract: The purpose of these studies was to compare directly the percutaneous absorption, excretion and metabolism of all-trans-retinoyl Β-glucuronide (RAG), a nontoxic retinoid, with all-trans-retinoic acid (RA) in the rat. Previously, it was demonstrated that topical treatment of human acne with either RAG or RA in cream resulted in a significant reduction of lesions. Whereas 0.1 % RA showed adverse effects, concentrations of RAG up to 2.4% did not cause any adverse reactions. In the present studies, radiolabeled RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Endogenous concentrations of ATRA in humans following topical administration of ATRA remain unchanged (Buchan et al 1994). In addition, topical administration of ATRAG in humans does not lead to elevated retinoic acid plasma levels (Barua and Olson 1996). In cancer patients undergoing treatment with oral ATRA, the maximum plasma concentrations of this drug are in the high nanomolar or micromolar range (Regazzi et al 1997), comparable to the retinoid concentrations applied in our in vitro assays.…”
Section: Introductionsupporting
confidence: 49%
See 2 more Smart Citations
“…Endogenous concentrations of ATRA in humans following topical administration of ATRA remain unchanged (Buchan et al 1994). In addition, topical administration of ATRAG in humans does not lead to elevated retinoic acid plasma levels (Barua and Olson 1996). In cancer patients undergoing treatment with oral ATRA, the maximum plasma concentrations of this drug are in the high nanomolar or micromolar range (Regazzi et al 1997), comparable to the retinoid concentrations applied in our in vitro assays.…”
Section: Introductionsupporting
confidence: 49%
“…1) (Janick-Buckner et al 1991) and has been characterised as an endogenous metabolite of vitamin A (Dunagin et al 1965;Zile et al 1982;McCormick et al 1983). ATRAG induces retinoid-speci®c biological eects in several systems with activity less than or similar to that of ATRA (Zile et al 1987;JanickBuckner et al 1991;Mehta et al 1991;Gunning et al 1993Gunning et al , 1994; Barua and Olson 1996;Foerster et al 1996;Sass et al 1997). With respect to stimulation of dierentiation and inhibition of the growth of HL-60 cells, ATRAG also shows comparable activity, with less cytotoxicity however, than ATRA (Gallup et al 1987;Zile et al 1987;Janick-Buckner et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human studies, it was observed that daily application of 2.4% RAG did not result in any redness or other side effects [15]. In another study on rat skin, it was shown that the percutaneous absorption of topically applied tritium-labeled RAG and RA was very similar [19]. However, significant amounts of RA could be detected in treated skin on day 7 after tRA dosing, whereas little or no RAG was found on skin on day 7 after RAG dosing.…”
Section: Discussionmentioning
confidence: 98%
“…[12]. In a comparative study, the percutaneous absorption, metabolism and excretion of tritium-labeled RBG and retinoic acid in the rat were found to be similar, if not identical [13]. Because the skin type of Asian people is different from that of American people of European origin [14], a double-blind vehiclecontrolled study was conducted to evaluate the efficacy and toxicity of RBG cream for the treatment of facial acne in patients in the north-eastern state of Assam in India.…”
Section: Introductionmentioning
confidence: 95%